The Problems of Islamic Family Law in the Digital Era and Its Relevance to Renewal of the Compilation of Islamic Law - Musarrofa , Ita; Muttaqin, Husnul; Amaliyah, Ridha (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The digital era raises various problems and challenges in Family Law which is still conventional. For example, in terms of marriage contracts and administration, utilisation of assets from the digital economy and so on. This study discusses the problems of Indonesian Islamic family law in facing changes in the digital era and its relevance to the renewal of the Compilation of Islamic Law. This study uses a netnography method with a normative legal approach. The results show several realities that are problems in Indonesian Islamic family law in the digital era such as online marriage, digital marriage dowry, online sexual relations between husband and wife, online nusyuz and zina, online divorce and reconciliation and joint property based on cyberspace. This situation demands a renewal of Islamic family law in Indonesia, especially the Compilation of Islamic Law as material law in the Religious Courts. By using the feature of openness in the system theory of the maqasid shariah, the `urf of cyberspace is worthy of being used as a legal basis for the renewal of the Compilation of Islamic Law. Several articles in the Compilation of Islamic Law that need to be renewed are marriage witnesses, marriage contract, submission of dowry, husband's obligations, joint property of husband, reasons for divorce, examination of divorce lawsuits, procedures for reconciliation and procedures for implementing wills. This renewal is very important to achieve the objectives of the law, namely justice, certainty and legal benefits.